Transforming Subjectivities: Studies in Human Malleability in Contemporary Times - Cecilia Hansen Löfstrand; Kerstin Jacobsson (Routledge Studies in the Sociology of Work, Professions and Organisations, 2023)
This volume examines the transformation of subjectivities following contemporary societal trends with regulatory and administrative authorities targeting human subjectivity with the aim to transform it. It addresses the malleability of human subjectivity through rich qualitative analyses of how different governing attempts are received by the subjects themselves. While the scholarship on governmentality has so far produced an enormously useful body of literature on the ‘how’ aspect of governing, this book suggests that it has been prone to overestimate the degree to which our subjectivities are open to change. Combining ethnographic sensitivity with more traditional governmentality perspectives allows us to explore how governing attempts ‘land’ in the terrain targeted—human subjectivity—in actual social contexts, under specific forms of governing and rationality. In doing so, the book makes a distinctive contribution to a second generation of governmentality studies. It will appeal to social scientists with interests in governance, governmentality, social policy and the sociology of work.